Evaluation of renal cold ischemia–reperfusion injury with intravoxel incoherent motion diffusion-weighted imaging and blood oxygenation level-dependent MRI in a rat model - Ren, Yan; Chen, Lihua; Yuan, Yizhong; Xu, Jipan; Xia, Fangjie; Zhu, Jinxia; Shen, Wen (Frontiers in Physiology, 2023)
Purpose: Cold ischemia-reperfusion injury (CIRI) is one of the most serious complications following renal transplantation. The current study investigated the feasibility of Intravoxel Incoherent Motion (IVIM) imaging and blood oxygenation level-dependent (BOLD) in the evaluation of different degrees of renal cold ischemia-reperfusion injury in a rat model. Methods: Seventy five rats were randomly divided into three groups (N= 25 for each group): T0：sham-operated group, T2/T4: CIRI groups with different cold ischemia hours (2, 4 hours, respectively). The CIRI group rat model was established by left kidney cold ischemia with right nephrectomy. All the rats received a baseline MRI before the surgery. Five rats in each group were randomly selected to undergo an MRI examination at 1 hour, day 1, day 2 and day 5 after CIRI. The IVIM and BOLD parameters were studied in the renal cortex (CO) and medulla (M) followed by histological analysis to examine Paller scores, peritubular capillary (PTC) density, apoptosis rate and biochemical indicators to obtain the contents of serum creatinine (Scr) , blood urea nitrogen (BUN), superoxide dismutase (SOD) and malondialdehyde (MDA). Results The D, D*, PF and T2* values in the CIRI groups were lower than the sham-operated group at all timepoints (all P < 0.05). The prolonged cold ischemia times resulted in gradually lower D, D*, PF and T2* values (all P < 0.05). The D and T2* values of cortex and medulla in Group T0 and T2 returned to the baseline level (all P＞0.05) except Group T4. The D* and PF values of cortex and medulla in Group T2 and T4 still remained below the normal levels (all P < 0.05) except Group T0. D, D*, PF and T2* values were strongly correlated with histopathological (Paller scores, PTC density and apoptosis rate ) and the biochemistry indicators (SOD and MDA) (|r|>0.6, P < 0.001). D*, PF and T2* values were moderately to poorly correlated with some biochemistry indicators (Scr and BUN) (|r|<0.5, P < 0.05). Conclusions IVIM and BOLD can serve as noninvasive radiologic markers for monitoring different degrees of renal impairment and recovery after renal CIRI.